Power, potential, and pitfalls in global health academic partnerships: review and reflections on an approach in Nepal. Issue 1 (1st January 2017) - Citrin, David; Mehanni, Stephen; Acharya, Bibhav; Wong, Lena; Nirola, Isha; Sherchan, Rekha; Gauchan, Bikash; Karki, Khem Bahadur; Singh, Dipendra Raman; Shamasunder, Sriram; Le, Phuoc; Schwarz, Dan; et al.
ABSTRACT: Background : Global health academic partnerships are centered around a core tension: they often mirror or reproduce the very cross-national inequities they seek to alleviate. On the one hand, they risk worsening power dynamics that perpetuate health disparities; on the other, they form an essential response to the need for healthcare resources to reach marginalized populations across the globe. Objectives : This study characterizes the broader landscape of global health academic partnerships, including challenges to developing ethical, equitable, and sustainable models. It then lays out guiding principles of the specific partnership approach, and considers how lessons learned might be applied in other resource-limited settings. Methods : The experience of a partnership between the Ministry of Health in Nepal, the non-profit healthcare provider Possible, and the Health Equity Action and Leadership Initiative at the University of California, San Francisco School of Medicine was reviewed. The quality and effectiveness of the partnership was assessed using the Tropical Health and Education Trust Principles of Partnership framework. Results : Various strategies can be taken by partnerships to better align the perspectives of patients and public sector providers with those of expatriate physicians. Actions can also be taken to bring greater equity to the wealth and power gaps inherent within global health academic partnerships. Conclusions : This study provides recommendations gleaned from the analysis, with an aim towards both future refinement of the partnership and broader applications of its lessons and principles. It specifically highlights the importance of targeted engagements with academic medical centers and the need for efficient organizational work-flow practices. It considers how to both prioritize national and host institution goals, and meet the career development needs of global health clinicians.